2000
DOI: 10.1046/j.1365-2249.2000.01132.x
|View full text |Cite
|
Sign up to set email alerts
|

Over-expression of the decoy receptor 3 (DcR3) gene in peripheral blood mononuclear cells (PBMC) derived from silicosis patients

Abstract: Dysregulation of apoptosis, particularly in the Fas/Fas ligand (FasL) pathway, is considered to be involved in the pathogenesis of autoimmune diseases such as systemic lupus erythematosus (SLE). Recently, a soluble decoy receptor, termed decoy receptor 3 (DcR3), that binds FasL and inhibits FasL-induced apoptosis, has been identified. Silicosis is clinically characterized not only by respiratory disorders but by immunological abnormalities. We have found that serum soluble Fas (sFas) levels are elevated in sil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 33 publications
0
49
0
Order By: Relevance
“…DcR3 is overexpressed in malignant tumors arising from lung, colon, glioma, and gastrointestinal track; virus-associated lymphoma (1, 4 -7); as well as the PBMC of silicosis patients (8). In addition, high serum levels of DcR3 have been detected in many cancer patients (9) and are associated with poor prognoses (6).…”
Section: Ecoy Receptor 3 (Dcr3)mentioning
confidence: 99%
“…DcR3 is overexpressed in malignant tumors arising from lung, colon, glioma, and gastrointestinal track; virus-associated lymphoma (1, 4 -7); as well as the PBMC of silicosis patients (8). In addition, high serum levels of DcR3 have been detected in many cancer patients (9) and are associated with poor prognoses (6).…”
Section: Ecoy Receptor 3 (Dcr3)mentioning
confidence: 99%
“…We found that dysregulation of the Fas-mediated apoptotic pathway might play an important role in the pathogenesis of the immunological abnormalities found in silicosis patients 7,8,[17][18][19] . Therefore, it is suggested that the genesis of anti-topo I autoantibodies is associated with the abnormalities of apoptosis-related molecules in silicosis patients.…”
Section: Discussionmentioning
confidence: 84%
“…In addition, silicosis patients in the anti-topo I (+) group showed inverse correlations between the serum sFas levels and PaCO 2 values, although patients in the anti-topo I (−) group did not. Moreover, our previous studies 7,19) on dysregulation of the Fas/FasL pathway showed that the same series of patients with silicosis or SLE showed higher serum sFas levels and over-expres- sion of the decoy receptor 3 gene in peripheral blood mononuclear cells, while SSc patients did not. These findings suggest that the genesis of anti-topo I autoantibodies is related to pulmonary involvement or lung fibrosis associated with progression of silicosis, and that it may have little association with dysregulation of the Fas-mediated apoptotic pathway.…”
Section: Discussionmentioning
confidence: 91%
“…The weaker membrane Fas expressers (among lymphocytes) were identified to be weaker fas message expressers . The gene expression levels of extracellular inhibitor competing membrane Fas-FasL binding such as sFas, decoy receptor 3 (DCR3), and other alternatively spliced variants of the fas gene were higher in peripheral blood mononuclear cells (PBMC) from SILs than HVs (Otsuki, 2000a(Otsuki, , 2000b. The intracellular apoptosis-inhibitory genes including i-flice, sentrin, survivine and icad showed a lower expression in PBMC from SILs than HDs (Guo, 2001;Otsuki, 2000c).…”
Section: Alteration Of Fas/cd95 and Its Related Molecules In Silsmentioning
confidence: 99%